2019
DOI: 10.1016/j.healthplace.2019.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Mental, physical and social health benefits of immersive nature-experience for children and adolescents: A systematic review and quality assessment of the evidence

Abstract: In this systematic review, we summarised and evaluated the evidence for benefits of immersive nature-experience on children and adolescents' mental, physical and social health. An electronic search was performed for English language articles published between January 2004 and May 2017.Data were extracted from 84 publications that met the inclusion criteria. Study quality was assessed for a subset of the studies, i.e. controlled between-and within-subjects studies, using a systematic assessment scheme, and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(110 citation statements)
references
References 86 publications
1
104
0
5
Order By: Relevance
“…A systematic review by Mygind et al [26] of 84 studies, found similar outcomes for children and adolescents, relating to mental health improvements after an immersive nature experience. However, their review focused on children and adolescents with behavioural and/or emotional disturbances and employed a broader definition (linked to nature experience, rather than play).…”
Section: Introductionmentioning
confidence: 91%
“…A systematic review by Mygind et al [26] of 84 studies, found similar outcomes for children and adolescents, relating to mental health improvements after an immersive nature experience. However, their review focused on children and adolescents with behavioural and/or emotional disturbances and employed a broader definition (linked to nature experience, rather than play).…”
Section: Introductionmentioning
confidence: 91%
“…Evidence is also lacking to determine if the association between physical activity and health outcomes in children and adolescents varies by type (e.g., aerobic vs. muscle-strengthening), domain (e.g., leisure-time vs. physical education vs. transportation), or location (outdoor vs. indoor) of physical activity. The GDG identified emerging evidence suggesting that physical activity of any type is more beneficial when performed outdoors "in nature" than when the same activity is performed indoors [12]. In addition, the health benefits of play (i.e., unstructured physical activity) Table 2 Research recommendations for people living with cancer, type 2 diabetes, hypertension, and HIV…”
Section: Specific Research Recommendations During Pregnancymentioning
confidence: 99%
“…Broadly speaking, exposure to nature and green spaces is beneficial for children's mental, physical and social health and well-being (e.g. Chawla 2015;Gill 2014;Mygind et al 2019;Tillman et al 2018). More specifically, when outdoor spaces in childcare settings and schools are 'greened' (modified to improve biodiversity and increase affordances and access to natural elements), this improves mental health and well-being, reduces stress, and promotes social and emotional skills (Bell and Dyment 2008;Brussoni et al 2017;Chawla et al 2014;Dankiw et al 2020;van Dijk-Wesselius et al 2018).…”
Section: Outdoor Play In Naturementioning
confidence: 99%